Development of radio-controlled (RC) lawn mower / Muhammad Azizi Abd Aziz - Abd Aziz, Muhammad Azizi (2023)
Nowadays, the multiple development and technologies in the area of engineering is always make people’s daily life easier. However, there are concerns in the convenience of lawn mowing facilities. In the present, peoples still using manual lawn mower that sold in the market which leads to many problems to the user. Currently, mowing the lawn can be so tiring and consume a bunch of time which can be physically restrictive, particularly for people with limited mobility. Through this project, it will help user to lawn mowing just using controller. It will solve a lot of problem that users are facing nowadays.